Monoclinic to cubic phase transformation and photoluminescence properties in Hf1-xSmxO2 (x = 0-0.12) nanoparticles - Kumar S.; Rai S.B.; Rath C. (My University, 2025)
Bulk hafnium oxide (HfO2) exhibits the monoclinic phase at room temperature which transforms to tetragonal and cubic phases at 1700 and 2600 °C, respectively, under ambient conditions. For the first time, we observe a monoclinic to stable cubic phase transformation at room temperature in nanoparticles of HfO2 by incorporating Sm3+ ions up to 12 at. %. Although the monoclinic structure is retained at 1 at. % of Sm, a mixed phase of monoclinic and cubic is observed at intermediate Sm concentration (5-11 at. %). Le-Bail profile refinement of X-ray diffraction patterns confirms the monoclinic to cubic phase transformation with increasing Sm3+ ion concentration. While the significant difference in ionic radii of Sm3+ and Hf4+ ion induces strain in the lattice above 9 at. %, a lower valency of Sm produces oxygen vacancy leading to 8-fold coordination with Sm3+ ion and stabilizes the cubic phase at room temperature. Not only the particle size obtained from transmission electron micrograph (TEM) matches well with the size calculated from the Williamson-Hall plot, the lattice spacing estimated from high resolution TEM also confirms the monoclinic and cubic phases in HfO2 and Hf0.88Sm0.12O2, respectively. Apart from phase transformation induced by Sm3+ ions, photoluminescence studies demonstrate an excellent emission in near green and red regions in Hf1-xSmxO2 nanoparticles. A schematic energy band diagram has been proposed based on the excitation and emission processes involved in HfO2 and Hf0.99Sm0.01O2 nanoparticles. © 2018 Author(s).